2022
DOI: 10.1001/jamapediatrics.2022.2946
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Childhood Family Income Supplements on Adult Functioning

Abstract: IMPORTANCEDuring an ongoing longitudinal cohort study, a casino opening created a natural cash transfer experiment. Some participating families received income supplements, and others did not. The children in this study are now adults.OBJECTIVE To assess the long-term outcomes of family income supplements received in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Decades of research have examined direct cash transfer programs, particularly in low-resource settings. While research has convincingly shown positive health impacts related to significant, recurring cash assistance, [ 10 , 31 ] fewer rigorous studies have examined the impact of modest, one-time unconditional cash transfers in the USA [ 17 – 19 ]. Three large randomized trials examining one-time unconditional cash transfers (of $500–$2000) during the COVID-19 pandemic in the USA did not find significant effects on financial or psychological wellbeing, physical health, or other examined outcomes [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research have examined direct cash transfer programs, particularly in low-resource settings. While research has convincingly shown positive health impacts related to significant, recurring cash assistance, [ 10 , 31 ] fewer rigorous studies have examined the impact of modest, one-time unconditional cash transfers in the USA [ 17 – 19 ]. Three large randomized trials examining one-time unconditional cash transfers (of $500–$2000) during the COVID-19 pandemic in the USA did not find significant effects on financial or psychological wellbeing, physical health, or other examined outcomes [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 This latest report from the Great Smoky Mountains Study, which followed up the participants up to ages 25 to 30 years, is remarkable in that childhood cash transfers had lasting benefits well into adulthood. 1 Those adults whose families received cash transfers reported fewer anxiety, depressive, and cannabis symptoms, fewer risky or illegal behaviors, as well as improved physical health and financial well-being. Children whose families received cash transfers for the longest periods and whose families received the largest amounts of cash had the lowest level of symptoms and the highest functioning, demonstrating a clear dose effect.…”
mentioning
confidence: 98%
“…8 It is important to factor these costs into any calculation of the cost of cash transfers to needy families, such as those described in this study. 1 Income-based childhood poverty is associated with many other disadvantages that may be harmful to children, including low parental education. Are the differences in outcomes between children in lower vs higher income groups children due to family income or to other threats that are correlated with income poverty?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Children receiving larger transfers for longer periods benefited the most. 6 How income supplementation may deliver longer-term health benefit is not always obvious, but careful analysis suggests subtle but potent mechanisms. For example, extra income allowed Native American mothers to provide greater supervision of children, resulting in better school attendance and grades and less involvement with criminal justice.…”
mentioning
confidence: 99%